ОЦІНКА ВПЛИВУ ЧАСТОТНИХ АВТОМАТИК ЕНЕРГОБЛОКІВ АТОМНИХ ЕЛЕКТРОСТАНЦІЙ НА ЖИВУЧІСТЬ ТА СТІЙКІСТЬ ОЕС УКРАЇНИ ЗА ЧАСТОТОЮ - Павловський, В.В.; Стелюк, А.О. (Інститут електродинаміки НАН України, Київ, 2015)
The problem of the frequency stability in the event of blackout in the interconnected power system (IPS) of Ukraine has been considered. The development of the detailed model of IPS of Ukraine considering the frequency emergency devices of the nuclear power plant (NPP) units and power system is substantiated. The models of the power unit frequency protection of the NPPs and loadshedding devices have been proposed. The simulation results of these devices operation are shown in the event of two units disconnection with the installed capacity of 2000 MW. References 9, figures 5.